Issues of the day of European Union. Expansion of European Union - Теремцова, Ніна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
An author is consider pressing questions, touching the problems of European Union, expansion of EU, the questions of history of European integration are affected.